Modern conditions for reproduction of the educational potential of the Russian workforce - O. A. Komarova (Вестник университета)
The relevance of the research is related to the need to substantiate the specifics of reproduction of the educational potential of workforce as a key resource that ensures generation of new knowledge, its successful implementation into practice, and innovative development of domestic enterprises. The purpose of the article is to identify and analyse modern conditions for the reproduction of the educational potential of the workforce. The research methodology is based on the use of an integrated and systematic approach to determining them, comparative and statistical methods of analysis. As conditions for the formation of the educational potential in the post-industrial era, the article considers: demographic conditions, globalisation, formation of a unified information space, and digitalisation of the economy, increasing demand for skilled labour, accelerated development of the service sector, and increase in labour migration. The results of the analysis show that in Russia, the reproduction of the educational potential is hampered as a result of the demographic crisis manifested in the continuation of the trend towards natural population decline and an increase in the number of people of retirement age; increase in the scale of external migration of skilled labour; average level of Internet accessibility to the population, and, as a result, insufficient formation of its digital skills. Attention is focused on the growing need of the national economy for personnel with a high educational and qualification level, digital skills, and information culture due to the formation of a unified information space and digitalisation of the economy, accelerated development of the service sector, globalisation, and the increasing role of universities in shaping the general culture of the population. The prospects for further research are to develop an organisational and economic mechanism for reproducing the educational potential of the workforce.